Effect of Obesity on Knee and Ankle Biomechanics during Walking - Paolo Capodaglio (MDPI AG, 2021)
The purpose of this retrospective study was to quantify the three-dimensional knee and ankle joint kinematics and kinetics during walking in young participants with different degrees of obesity and to identify the associated effects by stratifying the obese participants according to their BMI. Thirty-two young obese individuals (mean age 30.32 years) and 16 normal-weight age-matched individuals were tested using 3D gait analysis. Analysis of kinematic and kinetic data revealed significant differences in mechanics at knee and ankle joints in all the evaluated planes of movement. Compared to the healthy-weight participants, obese adults demonstrated less knee flexion, greater knee ab-adduction angle during the entire gait cycle and abnormalities at the knee flex-extension moment. At the ankle joint, reduced range of motion was observed together with a lower peak of ankle plantarflexor moment and power during terminal stance. These results provide insight into a potential pathway by which obesity predisposes a healthy adult for increased risk of osteoarthritis.